Synthesis of a Novel Series of Cu(I) Complexes Bearing Alkylated 1,3,5-Triaza-7-phosphaadamantane as Homogeneous and Carbon-Supported Catalysts for the Synthesis of 1- and 2-Substituted-1,2,3-triazoles - Ivy L. Librando; Abdallah G. Mahmoud; Sónia A. C. Carabineiro; M. Fátima C. Guedes da Silva; Carlos F. G. C. Geraldes; Armando J. L. Pombeiro (Nanomaterials, 2021)
The N-alkylation of 1,3,5-triaza-7-phosphaadamantane (PTA) with ortho-, meta- and para-substituted nitrobenzyl bromide under mild conditions afforded three hydrophilic PTA ammonium salts, which were used to obtain a new set of seven water-soluble copper(I) complexes. The new compounds were fully characterized and their catalytic activity was investigated for the low power microwave assisted one-pot azide–alkyne cycloaddition reaction in homogeneous aqueous medium to obtain disubstituted 1,2,3-triazoles. The most active catalysts were immobilized on activated carbon (AC), multi-walled carbon nanotubes (CNT), as well as surface functionalized AC and CNT, with the most efficient support being the CNT treated with nitric acid and NaOH. In the presence of the immobilized catalyst, several 1,4-disubstituted-1,2,3-triazoles were obtained from the reaction of terminal alkynes, organic halides and sodium azide in moderate yields up to 80%. Furthermore, the catalyzed reaction of terminal alkynes, formaldehyde and sodium azide afforded 2-hydroxymethyl-2H-1,2,3-triazoles in high yields up to 99%. The immobilized catalyst can be recovered and recycled through simple workup steps and reused up to five consecutive cycles without a marked loss in activity. The described catalytic systems proceed with a broad substrate scope, under microwave irradiation in aqueous medium and according to “click rules”.